Pro Android Games - Silva, Vladimir (Apress : Imprint: Apress, 2012)
In the last few years, Android has progressed with the debut of better fonts, new User Interface and Experience (UI/UX) APIs, tablet considerations, multi-touch capabilities, multi-tasking, faster performance, improved battery management techniques, and now Google TV Android Apps for the Android game app developer repertoire.  With actionable real-world source, Pro Android Games, Second Edition shows you how to build more sophisticated and addictive Android games, by leveraging the power of these recent advancements found in the new Android Jelly Beans development platform as well as those you've counted on in earlier releases. Multi-touch code gives these games and their players dynamic input and exchange ability, for a more realistic arcade game experience. Faster and better performance offers game players a more seamless, fun arcade experience like never before on Android. There is also improved native C/C++ integration with Android's NDK as well, which makes coding, compiling, and converting both productive and efficient with gains in app performance.  *** NOTE:  This book published previously as Advanced Android 4 Games.  This edition covers game development for all Android SDK versions up to Jelly Bean / Android SDK 4.1. Pro Android Games, Second Edition features the following improvements:  Updates to the latest version of the Android SDK, NKD, plus the latest Eclipse IDE. Greater focus on tablets the ever changing device resolutions, and hardware specs.  Native game development and hardware accelerated graphics. Bigger and Better Real World Engines, such as Quake I and II Plus an oldie from the previous edition: Doom Coverage of the new smart TV APIs (Google TV), UI, UX, multi-touch and multi-tasking features available with Android Jelly Bean. A look into the future with augmented reality Advanced techniques for improving your game playing experience including better multi-tasking, improved performance optimization, battery management and more. A "Quake 3D"-like game app case study  You'll definitely have fun, and perhaps you'll even make some money. Enjoy!